CHEMICAL CONSTITUENTS AND LARVICIDAL ACTIVITY OF VOLATILE OIL FROM Solenostemon monostachyus (P Beauv.) Briq. AGAINST Anopheles gambiae - R., ATIKO,; A., KWAJI,; A. A., MUSA, (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2022)
Synthetic larvicides have been used to control malarial vector. However, increasing resistance of mosquito larvae to the synthetic larvicides poses great problem in the vector control. Natural control with plant essential oil may serve as an alternative. This study investigates the chemical constituents and larvicidal activity of volatile oil obtained from Solenostemon monostachyus against the larvae of Anopheles gambiae. The volatile oils were extracted using hydro-distillation in a Clevenger type apparatus and analyzed using GC-MS. The larvicidal assay was carried out against Anopheles gambiae larvae at concentration range of 12.5- 400 μg/mL. The analysis of the volatile oil showed that the major constituents of the oil were Caryophyllene oxide (21.6%), β-Caryophyllene (19.6%), β-Pinene (9.8%) and Germacrene D (7.3%). Results showed that larval mortality increases with increasing exposure period to the volatile oils from S. monostachyus. The larvicidal activity demonstrated that the mosquito larvae were susceptible to the volatile oil with LC50 of 23.44 μg/mL. The results suggest that S. monostachyus essential oil has potentials for the control of Anopheles gambiae. Therefore the plant may serve as a potential source of raw material for a new and eco-friendly larvicide.